A VIEW ON THE TECHNIQUES OF TEACHING SPEAKING - admin admin; Mansur mansur (Universitas Muhammadiyah Gresik, 2012)
Teaching English skills to learners become a important issue nowdays. English teachers should concern to the importance of motivating their students to master the language skills. In fact, it is not easy to teach all the skills especially productive skill, speaking and writing. Teaching speaking in the classroom needs varieties of teaching techniques in order that the learners are active in the teachinglearning process in the classroom. English teachers should choose the techniques which are appropriate with situations and conditions in the class. They have to consider how to create a conducive atmosphere so that all learners are actively involve in speaking activities. In this short article, the writer suggests some theories of teaching speaking which are proposed by some wellknown teaching experts. It is hoped that by reading this short article, readers (English teachers) would find benefit from it.